Acute mercury poisoning complicated by gastrointestinal bleeding - Bhattacharjee, Manna; Mahawar, Ashok K.; Paghdar, Harshkumar (International Journal of Advances in Medicine, 2024)
Mercury poisoning is a rare but potentially serious condition that can result from environmental exposure to elemental mercury. We present a case of a 22-year-young male who presented to the emergency department (ED) with symptoms of mercury poisoning after his family members brought home a vial of elemental mercury. The patient experienced nausea, anxiety, abdominal pain, diarrhea, and fever. Despite normal initial laboratory tests and imaging studies, a presumptive diagnosis of mercury poisoning was made based on the patient’s history of exposure and clinical presentation. Although his hospital stay was complicated by passage of blood in stool, possibly lower GI bleed, but treatment with N-acetylcysteine (NAC) was initiated empirically, leading to resolution of symptoms and a favorable outcome. This case highlights the importance of considering mercury poisoning in patients with appropriate exposure history and the effectiveness of NAC in the treatment of acute mercury poisoning. Public education on the hazards of mercury and the importance of prompt recognition and treatment are essential in preventing severe complications associated with mercury exposure.